RETRACTED: Electrospun Ta-MOF/PEBA Nanohybrids and Their CH4 Adsorption Application - Jasim, Saade Abdalkareem; Hadi, Jihad M.; Jalil, Abduladheem Turki; Catalan Opulencia, Maria Jade; Hammid, Ali Thaeer; Tohidimoghadam, Mohadeseh; Moghaddam-manesh, Mohammadreza (Frontiers in Chemistry, 2022)
For the first time, biocompatible and biodegradable Ta-metal organic framework (MOF)/polyether block amide (PEBA) fibrous polymeric nanostructures were synthesized by ultrasonic and electrospinning routes in this study. The XRD peaks of products were wider, which is due to the significant effect of the ultrasonic and electrospinning methods on the final product. The adsorption/desorption behavior of the nanostructures is similar to that of the third type of isotherm series, which showed mesoporous behavior for the products. The sample has uniform morphology without any evidence of agglomeration. Since the adsorption and trapping of gaseous pollutants are very important, the application of the final Ta-MOF/PEBA fibrous polymeric nanostructures was investigated for CH4 adsorption. In order to achieve the optimal conditions of experiments and also systematic studies of the parameters, fractional factorial design was used. The results showed that by selecting temperature 40°C, time duration 35 min, and pressure 3 bar, the CH4 gas adsorption rate was near 4 mmol/g. Ultrasonic and electrospinning routes as well as immobilization of Ta-MOF in the PEBA fibrous network affect the performance of the final products for CH4 gas adsorption.